Emotional Control, Concern about Covid-19 and Consumer Behaviour in the Population of Lima - Torres Lajo, Manuel (2021)
This research’s objective is to establish whether the emotional control, the concern about COVID-19 and the consumer behaviour are related among them; as well as to establish the attitudes of the population from Lima, Peru towards the pandemic and its consumption habits. Three digital questionnaires were made, which were answered by 663 people from Lima. The results show that a significant relationship exists between emotional control and the concern about COVID-19; but there is not one between such concern and the consumer behaviour. On the other side, the descriptive results do show changes in the consumer behaviour as a result of the pandemic. These results lead to the conclusion that, even though COVID-19 is still a concern for the population, it is highly likely that the initial fear has been controlled either due to adaptation to the new normality or due to the imperious necessity to go out to work to survive.